Duloxetine in Practice-Based Clinical Settings: Assessing Effects on the Emotional and Physical Symptoms of Depression in an Open-Label, Multicenter Study - Wohlreich, Madelaine M. (Physicians Postgraduate Press, Inc., 2007)
Objective: In placebo-controlled clinical trials, duloxetine has been shown to be effective and well-tolerated in patients with major depressive disorder (MDD). However, patients in registration trials may not be representative of patients in clinical practice. This study sought to assess the effectiveness, safety, and tolerability of duloxetine in diverse populations of outpatients with MDD. Method: This open-label study recruited out-patients ≥ 18 years of age with DSM-IV MDD in primary care or psychiatric practice settings and treated them with duloxetine 60 mg q.d. for 7 weeks. Primary outcome measures were (1) the physicianrated Clinical Global Impressions-Severity of Illness scale, (2) the patient-rated 28-item Somatic Symptom Inventory (SSI-28) average, and (3) the patient-rated 16-item Quick Inventory of Depressive Symptomatology-Self Report. Quality of life, disability, and vital signs also were assessed. The first patient visit was August 16, 2004. The last patient visit was January 7, 2005. Results: Of 3543 outpatients enrolled, 3431 received at least 1 dose of duloxetine, of whom 71.4% completed the study. Most patients were Caucasian (90.8%) and female (75.4%); mean age was 48 years. Duloxetine significantly (p < .001) improved all efficacy measures in all treated patients as well as in subgroups based on gender, ethnic origin, age, and patient care setting. Except for the SSI-28 average, all the efficacy measures were in favor of female gender and primary care subgroups. Overall, 10.8% of patients discontinued due to adverse events. Conclusion: Duloxetine 60 mg q.d. was effective, regardless of gender, ethnic origin, age, and patient care settings, in this 7-week open-label study and was well-tolerated in a diverse population of outpatients with MDD. Clinical Trials Registration: ClinicalTrials.gov identifier NCT00479726.